Obiekty życia kulturalnego w Ciechocinku w XIX wieku. Teatr - Kania, Agnieszka (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
In the 19th century seasonal trips to health resorts were very common. People would venture there not only for health reasons but mostly to relax and have fun. Development of western health resorts was very rapid and the service-providing objects were built on the great scale there. Many of them were located also on the ex-polish grounds, due to Partitions. One of the largest and mostly visited resorts was located in Ciechocinek. Owners were forced to successively develop new balneological and cultural offer to raise its competitiveness and attractiveness. One of the strongest points of local entertainment was the theatre. The paper discusses the history of consecutive theatre stages, located in Ciechocinek. It also highlights many challenges that the pioneers had to overcome. Often theatre owners confronted by low funding were forced to delay new investment by years while modifying initial plans to make them far less complicates. The very first theatres in Ciechocinek were very modest. They were initially housed in sheds or adapted barns. The first purpose built theatre – so called Summer Theatre – was built in the 80s /90s of the 19th century. Almost 50 years after the foundation of the resort. The article also describes the complicated situation of theatre crews and spectators attendance during plays.